TRADITIONS, LAND RIGHTS, AND LOCAL WELFARECREATION: STUDIES FROM EASTERN INDONESIA - Sulistiawati, Linda Yanti (2015)
The research sets a focus on current economic impacts of traditional systems of land distribution and user rights among households, clans and the government. Sites for research are selected in two of the poorest provinces of Indonesia, NusaTenggara Timur and Maluku. One main objective of the research is to reveal local social and political mechanisms behind preserved social and gender injustice and barriers to economic progress. Another goal is to discuss political and administrative alternatives for dividing and governing productive land to meet new needs in the management of agriculture and forestry and for the development of modern infrastructure and businesses. A mixed research methodology is applied: both qualitative, in-depth interviews with a variety of key informants, and a quantitative approach including survey interviews with a total of 600 randomly selected respondents from households at nine different studysites in each of the two provinces. Preliminary findings indicate that an increasing number of land conflicts occur in the study areas. Our policy recommendations include a transfer to formalized and taxable clan ownership with specified and registered family user rights. Key Words: ‘sleeping land’, communal ownership, land conflicts, user rights